Erythropoietin Administration Increases Production and Reactivity of Platelets in Dogs - Wolf, Roman F; Peng, Jinpeng; Friese, Paul; Gilmore, Laura S; Burstein, Samuel A; Dale, George L (Thrombosis and Haemostasis, 1997)
Administration of erythropoietin (EPO) to adult dogs resulted in a dramatic increase in the number of thiazole orange-positive (TO+) platelets, also referred to as reticulated platelets. Pre-treatment level of TO+ platelets was 6.2 ± 0.5% (mean ± 1 SE; n = 5); following day 5 of treatment with 500 U EPO/kg/day, the percentage of TO+ platelets peaked at 16.8 ± 2.3% (n = 5; p <0.02). After cessation of the hormone, the number of TO+ platelets fell rapidly to below starting levels. Unexpectedly, there was a significant decline in total platelet count during EPO administration despite an increased level of TO+ platelets. To assess platelet reactivity, total platelets and TO+ platelets from EPO- treated dogs were analyzed for thrombin-responsiveness as quantitated by P-selectin expression on the cell surface; reactivity was expressed as a thrombin EC50, the thrombin concentration required to activate 50% of platelets. Both total and TO+ platelets were hyperreactive during EPO treatment when compared either to pre-treatment values or to control animals. Thrombin EC50 values for total and TO+ platelets on day 5 fell to 66.5 ± 5.4% (mean ± 1 SE; n = 5; p <0.02) and 62.2 ± 8.7% (n = 5; p <0.025), respectively, of pre-treatment levels. These data indicate that EPO not only promotes the synthesis of increased numbers of TO+ platelets in the dog but that these newly produced platelets are hyperreactive when compared to TO+ platelets from control animals.